Signalling to chromatin through post-translational modifications of HMGN. - Pogna, E; Clayton, A; Mahadevan, L (2010)
The DNA of eukaryotic genomes is highly packaged by its organisation into chromatin, the fundamental repeating unit of which is the nucleosome core particle, consisting of 147 base pairs of DNA wrapped around an octamer of two copies each of the four core histone proteins H2A, H2B, H3 and H4 (K. Luger, A.W. Mader, R.K. Richmond, D.F. Sargent, T.J. Richmond, Crystal structure of the nucleosome core particle at 2.8 A resolution, Nature 389 (1997) 251-260 [1] and references therein). Accessibility of DNA within chromatin is a central factor that affects DNA-dependent nuclear function such as transcription, replication, recombination and repair. To integrate complex signalling networks associated with these events, many protein and multi-protein complexes associate transiently with nucleosomes. One class of such are the High-Mobility Group (HMG) proteins which are architectural DNA and nucleosome-binding proteins that may be subdivided into three families; HMGA (HMGI/Y/C), HMGB (HMG1/2) and HMGN (HMG14/17). The structure of chromatin and nucleosomes can be altered, both locally and globally, by interaction with such architectural proteins thereby influencing accessibility of DNA. This chapter deals with the HMGN protein family, specifically their post-translational modification as part of regulatory networks. We focus particularly on HMGN1, the most extensively studied family member to date, and to a lesser extent on HMGN2. We critically evaluate evidence for the role of post-translational modification of these proteins in response to different signals, exploring the sites and potential significance of such modification.